Effectiveness of cognitive behavioural therapy on pain of patients with low back pain - Sudha BANTH; Maryam Didehdar ARDEBiL (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Background: Chronic low back pain is a major health problem and has high comorbidity with psychological related disorders. As there is no consensus about the effectiveness of psychotherapy methods for chronic pain, so our target in this study was to assess the efficacy of cognitive behavioral therapy (CBT) as a psychological intervention on pain of female patients with nonspecific chronic low back pain (NSCLBP). Methods: 88 patients suffering from NSCLBP were randomly assigned to experimental and control groups, CBT (CBT+ usual medical care) and usual medical care, respectively. The subjects were referred from physiotherapy centres of Ardebil (northwest of Iran), assessed at three time frames; before, after and four weeks after intervention by pain Mac Gil Pain questionnaire. Data obtained from the final sample (N=48) analysed by SPSS software. Results: The results of ANCOVA revealed that subjects in the CBT group in comparison to control group indicated significant improvements in pain. Effect sizes were .72 and .78 for post test 1 and post test 2 of evaluation respectively. Conclusion: CBT as a psychotherapy including cognitive restructuring, relaxation and daily home works was effective on physical on several pain senses of female Iranian patients with NSCLBP